Le donne nei fenomeni di migrazione irregolare, tratta e traffico di esseri umani - CIURLO, ALESSANDRA (Gregorianum, 2018)
The increasing presence of women in the various configurations of migratory processes is not yet accompanied by greater attention to their specific problems and to the dynamics that characterize their migratory movements. The article analyzes the female dimension in irregular migration, people-smuggling and trafficking in human beings as an attempt to overcome the gender-neutral approach that has prevailed over time and which does not reveal the particularities of the female experience. The considerations set out in the text highlight the need for greater equality for women and remind of the need for the adoption of a gender approach both for the analysis of migratory phenomena and for their treatment.